2009
DOI: 10.1111/j.1467-9280.2009.02426.x
|View full text |Cite
|
Sign up to set email alerts
|

Weight as an Embodiment of Importance

Abstract: Four studies show that the abstract concept of importance is grounded in bodily experiences of weight. Participants provided judgments of importance while they held either a heavy or a light clipboard. Holding a heavy clipboard increased judgments of monetary value (Study 1) and made participants consider fair decision-making procedures to be more important (Study 2). It also caused more elaborate thinking, as indicated by higher consistency between related judgments (Study 3) and by greater polarization of ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
307
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 331 publications
(330 citation statements)
references
References 12 publications
19
307
1
3
Order By: Relevance
“…One possible reason that the valence of stimuli did not interfere with brightness categorizations might have been that participants did not process the affective meaning of the words before categorizing them on their brightness. More recent studies reveal that the moral meaning of stimuli can interfere with the correct categorization of the brightness of words (Sherman & Clore, 2009), and several studies have revealed a bi-directional association between concepts such as weight and importance (Jostmann, Lakens, & Schubert, 2009;Schneider, Rutjens, Jostmann, & Lakens, in press) or affection and warmth (IJzerman & Semin, 2010;Williams & Bargh, 2008;Zhong & Leonardelli, 2008). The circumstances under which the relationship between perceptual and conceptual dimensions is asymmetric remains a question for further research.…”
Section: Open Questionsmentioning
confidence: 99%
“…One possible reason that the valence of stimuli did not interfere with brightness categorizations might have been that participants did not process the affective meaning of the words before categorizing them on their brightness. More recent studies reveal that the moral meaning of stimuli can interfere with the correct categorization of the brightness of words (Sherman & Clore, 2009), and several studies have revealed a bi-directional association between concepts such as weight and importance (Jostmann, Lakens, & Schubert, 2009;Schneider, Rutjens, Jostmann, & Lakens, in press) or affection and warmth (IJzerman & Semin, 2010;Williams & Bargh, 2008;Zhong & Leonardelli, 2008). The circumstances under which the relationship between perceptual and conceptual dimensions is asymmetric remains a question for further research.…”
Section: Open Questionsmentioning
confidence: 99%
“…This contention has received mounting empirical support in recent years: the experience of physical warmth activates the concept of interpersonal warmth (Williams & Bargh, 2008), and contact with a physically hard object elicits firmness or rigidity in negotiation (Ackerman, Nocera, & Bargh, 2010). Finally, in a test of the association between physical and conceptual weight, participants who held a heavy clipboard rated various issues as more important relative to those who made their ratings while holding a light clipboard (Ackerman et al, 2010;Jostmann, Lakens, & Schubert, 2009). The reasons underlying these various effects may diverge -a functionalist account for biases in visual perception guiding action (Gibson, 1979); metaphoric priming as a developmental artifact of using sensorimotor information to learn higher-order reasoning (Williams, Huang, & Bargh, 2009) -but the relevance of physical experience remains consistent.…”
mentioning
confidence: 99%
“…Embodied cognition research has 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 The Illusion of Nonmediation in Telecommunication 15 demonstrated that some deeply learned associations could influence judgments even when the perceptual cues are contextually irrelevant (for a review, see Barsalou, 2008). For instance, people were found to treat a questionnaire as more important when they held a heavier compared to a lighter clipboard (Jostmann, Lakens, & Schubert, 2009). The association between physical weight and importance is well learnt so processing the former is likely to activate the latter (cf.…”
Section: Discussionmentioning
confidence: 99%